2021
DOI: 10.7717/peerj.11984
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral phenotyping of cancer pain in domesticated cats with naturally occurring squamous cell carcinoma of the tongue: initial validation studies provide evidence for regional and widespread algoplasticity

Abstract: Feline oral squamous cell carcinoma (FOSCC) is a common and naturally occurring condition that recapitulates many features of human head and neck cancer (HNC). In both species, there is need for improved strategies to reduce pain caused by HNC and its treatment. Research to benefit both species could be conducted using pet cats as a comparative model, but this prospect is limited by lack of validated methods for quantifying FOSCC-associated pain. A prospective non-randomized pilot study was performed for initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Referred pain and widespread pain have been reported in patients with HNC (Cuffari et al 2006;van den Beuken-van Everdingen et al 2007;Hechler et al 2020) and in animals with oral cancer (Chodroff et al 2016;Ye et al 2017;Lai et al 2021), which suggest the involvement of central sensitization. Although referred pain could also be attributed to peripheral mechanisms such as satellite glia activation (Shinoda et al 2019) and cross-sensitization of nerves adjacent to the nerve innervating the injury site (Boada et al 2015;Gutierrez et al 2021), microglia-mediated central sensitization has been reported in rats with tongue SCC (Tamagawa et al 2016).…”
Section: Central Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…Referred pain and widespread pain have been reported in patients with HNC (Cuffari et al 2006;van den Beuken-van Everdingen et al 2007;Hechler et al 2020) and in animals with oral cancer (Chodroff et al 2016;Ye et al 2017;Lai et al 2021), which suggest the involvement of central sensitization. Although referred pain could also be attributed to peripheral mechanisms such as satellite glia activation (Shinoda et al 2019) and cross-sensitization of nerves adjacent to the nerve innervating the injury site (Boada et al 2015;Gutierrez et al 2021), microglia-mediated central sensitization has been reported in rats with tongue SCC (Tamagawa et al 2016).…”
Section: Central Mechanismsmentioning
confidence: 95%
“…Oral SCC is a common and naturally occurring condition in domestic cats that exhibits similar features to HPV – oral SCC in humans (Lai et al 2021). Using a combination of pet owner–administered QOL questionnaire and visual assessment scoring tool, a vet assessment questionnaire, and 2 mechanical quantitative sensory testing (QST) methods (electronic von Frey and Cochet–Bonnet), the authors show that cats with tongue cancer exhibit increased mechanical sensitivity around the face and cornea, as well as reduced mechanical thresholds at distant body sites, which can be reversed by the analgesic buprenorphine.…”
Section: Preclinical Models Of Hnc Painmentioning
confidence: 99%